Perancangan dan Implementasi Sistem Aplikasi untuk Meningkatkan Efisiensi dan Efektivitas Kegiatan Lembaga Riset dan Pengabdian Masyarakat (LRPM) - Ramayanti, Desi; Hidayat, Ryan; Hanafi, Muhammad; Apriani, Ari (JSAI (Journal Scientific and Applied Informatics), 2024)
This study aims to develop an efficient and effective information system for the Research and Community Service Institute (LRPM) using the Rapid Application Development (RAD) method. RAD was chosen for its capability to produce rapid system development with iterations that allow adaptation to changing needs. The research methodology includes planning, design, implementation, and system testing. The system development involved the use of PHP with Laravel as the framework and MySQL as the database. The results indicate that the developed LRPM information system successfully met all the predefined functional requirements, including modules for login, registration, proposal submission, proposal tracking, and data management by the admin. System testing using the black box testing method resulted in a functionality score of 100%, indicating that the system operates according to expectations and is ready for use. This system is expected to improve efficiency and effectiveness in managing research and community service activities at LRPM.